Pengaruh Pajak, Multinasionalitas dan Leverage Terhadap Transfer Pricing Pada Perusahaan Sub Sektor Batu Bara - Aprelia Novita Dewi; Fadjar Harimurti; Djoko Kristianto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Transfer pricing is a policy that is usually used by companies in determining the price of a transaction between parties who have a special relationship. In order to carry out Transfer Pricing, companies can use several indicators, Tax, Multinationality, and Leverage. This research aims to analyze the significance of the influence of Tax, Multinationality and Leverage on Transfer Pricing listed in Bursa Efek Indonesia 2019-2022 period. This research uses secondary data, the data source used is financial reports. The population in this study are coal sub-sector companies registered in Bursa Efek Indonesia 2019- 2022 period. The sample used in this research was 8 coal sub-sector companies selected using the purposive sampling method. The data collection method used is documentation techniques. The data analysis technique uses multiple linear regression analysis. The research results show that taxes have an effect on transfer pricing, while multinationality and leverage have no effect on transfer pricing.